Experiment and Simulation Study on the Amorphous Silicon Photovoltaic Walls - Wenjie Zhang; Bin Hao; Nianping Li (International Journal of Photoenergy)
Based on comparative study on two amorphous silicon photovoltaic walls (a-Si PV walls), the temperature distribution and the instant power were tested; and with EnergyPlus software, similar models of the walls were built to simulate annual power generation and air conditioning load. On typical sunshine day, the corresponding position temperature of nonventilated PV wall was generally 0.5~1.5°C higher than that of ventilated one, while the power generation was 0.2%~0.4% lower, which was consistent with the simulation results with a difference of 0.41% in annual energy output. As simulation results, in summer, comparing the PV walls with normal wall, the heat per unit area of these two photovoltaic walls was 5.25 kWh/m2 (nonventilated) and 0.67 kWh/m2 (ventilated) higher, respectively. But in winter the heat loss of nonventilated one was smaller, while ventilated PV wall was similar to normal wall. To annual energy consumption of heating and cooling, the building with ventilated PV wall and normal wall was also similar but slightly better than nonventilated one. Therefore, it is inferred that, at low latitudes, such as Zhuhai, China, air gap ventilation is suitable, while the length to thickness ratio of the air gap needs to be taken into account.